Significance of zinc fertilization and microbial inoculation on phosphorus nutrition of rice (Oryza sativa) - SHAHANE, A A; SHIVAY, Y S; KUMAR, D; PRASANNA, R (The Indian Journal of Agricultural Sciences, 2020)
The present experiment was conducted during rainy season of 2013-14 at ICAR–Indian Agricultural Research Institute, New Delhi, to compare and calculate variations in phosphorus (P) concentration and uptake in rice (Oryza sativa L.) plant as well as soil available P (Olsen’s reagent 0.5 M NaHCO3-extractable) as influenced by three different crop establishment methods (CEMs), rates of nitrogen (N), phosphorus (P) and zinc (Zn) fertilization and microbial inoculations in spilt plot design with three replications. The concentration and uptake of P in puddled transplanted rice (PTR) and system of rice intensification (SRI) was significantly higher than aerobic rice system (ARS) and total uptake was increased by 480 and 540 g/ha in PTR and 580 and 660 g/ha in SRI over ARS in first and second year, respectively. The treatment with 100% recommended dose of nutrients (RDN) (25.8 kg P/ha and 120 kg N/ha) had significantly higher P concentration and uptake than 75% RDN and absolute control. The correlation between milled rice yield and P concentration was found positive (R2= 0.95 and 0.94). Application of microbial inoculation significantly increased P concentration and uptake over fertilizer control (75% RDN) and absolute control which increased in total P uptake by 640 and 680 g/ha due to application of Anabaena–Pseudomonas (An-Ps) biofilmed formulations (MI2) and Anabaena sp. (CR1) + Providencia sp. (PR3) consortia (MI1) over fertilizer control (75% RDN).